2011
DOI: 10.1177/1010539511430521
|View full text |Cite
|
Sign up to set email alerts
|

Does Ethnicity Contribute to the Control of Cardiovascular Risk Factors Among Patients With Type 2 Diabetes?

Abstract: This study aimed to examine the control of cardiovascular risk factors among the ethnic groups with type 2 diabetes in Malaysia. The authors analyzed the data of 70 092 adults from the Malaysian diabetes registry database. Malays had the worst achievement of target for most of the risk factors. Indians had poor achievement of control for waist circumference (odds ratio [OR] = 0.6, 95% confidence interval [CI] = 0.6-0.7) and high-density lipoprotein cholesterol (OR = 0.5, 95% CI = 0.4-0.5). As compared with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 24 publications
2
9
0
Order By: Relevance
“…Assuming a standard and common A1C goal of 7% for all patients, the excess mean A1C of 1.07% in 2017 represented 22.5% higher risks of diabetes-related endpoints in our patients 6,17 . These morbidity and mortality outcomes may be preventable if additional attention is given to control their glycaemia 9 In this study, Chinese ethnic patients had the overall best A1C control compared to Malays and Indians, as reported in a previous study 33 . Post hoc analysis showed that Chinese ethnic patients had the lowest percentage of loss to follow-up, which may imply better health behaviour.…”
Section: Discussionsupporting
confidence: 63%
“…Assuming a standard and common A1C goal of 7% for all patients, the excess mean A1C of 1.07% in 2017 represented 22.5% higher risks of diabetes-related endpoints in our patients 6,17 . These morbidity and mortality outcomes may be preventable if additional attention is given to control their glycaemia 9 In this study, Chinese ethnic patients had the overall best A1C control compared to Malays and Indians, as reported in a previous study 33 . Post hoc analysis showed that Chinese ethnic patients had the lowest percentage of loss to follow-up, which may imply better health behaviour.…”
Section: Discussionsupporting
confidence: 63%
“…(10,23) Glycaemic control was found to be worse among adults of Malay ethnicity, followed by those of Indian and Chinese ethnicities. (24) The proportion of Malaysians aged ≥ 60 years with HbA1c level ≥ 7.0% was 58.3%. (25) Adult Malaysians with poor glycaemic control were found to lack knowledge on diabetes mellitus and demonstrate inadequate self-care practices.…”
Section: Introductionmentioning
confidence: 97%
“…Malaysian data showed an increase in the prevalence of T2DM, a high number of diabetes-related complications and persistent poor disease control and management among T2DM patients [ 12 , 13 ], especially among the Malays [ 14 ]. Given the importance of illness perceptions for health behaviour and outcomes and given the rising burden of T2DM and its associated mood disorders in Malaysia [ 15 , 16 ], we translated and validated a Malay version of the Brief Illness Perception Questionnaire (MBIPQ) to facilitate the assessment of illness perceptions in a Malay-speaking population.…”
Section: Introductionmentioning
confidence: 99%